PERBANDINGAN KREDIT ANTARA BANK KONVENSIONAL DAN BANK SYARIAH PADA BANK MANDIRI DI SAMARINDA - ., Joanna (EKONOMIA, 2014)
Formulation of the problem of this research is whether Islamic bank making loans on more favorable compared to conventional bank.Taking credit in Islamic bank more profitable than taking credit in conventional bank. This study uses analysis techniques such us Net Present Value ( NPV )Based on the analysis and discussion revealed that the number of Net Present Value (NPV) credit Mandiri Bank is Rp. 106.635.323,07 whereas the total value of Net Present Value (NPV) credit Islamic Mandiri Bank is Rp. 106.427.280,00-. Thus the hypothesis put forward earlier if taking Islamic bank credit is more advantageous than conventional bank lines of credit at acceptable.